Remoção microbiológica de nitrogênio, fósforo, DQO e DBO em uma estação de tratamento de efluentes numa fábrica de concentrados de bebidas - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
It is essential that there is proper treatment of industrial wastewater before its release to the receiving body. Therefore, it is necessary to know which type of treatment to suit particular type of effluent generated, so that it can comply with the environmental regulations to prevent damage to the environment, such as water pollution. This study aimed to evaluate the efficiency of microorganisms to reduce the amount of organic matter (COD, BOD), nitrogen and phosphorus in an activated sludge system in an industry concentrates of non-alcoholic beverages during the period 2009 and 2010, featuring the effluent before and after analyzing the treatment, assessing also the major classes of microorganisms that participated in the process of removing nitrogen and phosphorus loads, BOD and COD, and statistically evaluate the process variables determining the ratio of the organic load factor / microorganisms. The physico-chemical analyzes were performed according to methods described in Standard Methods for the Examination of Water and Wastewater, 20th Edition (1998) and 21st Edition (2005). For data analysis techniques were used for statistical analysis of variance, and trend graphs and efficiency in order to check the possibility of optimizing the treatment. All data were tabulated and statistical methods were applied using Minitab software version 14.0. The results were analyzed using boxplots for the years 2009 and 2010, where there was greater removal efficiency for the parameters of color, COD, BOD and phosphorus. Correlated result Nitrogen ammonia versus Total Nitrogen, in which we observed greater efficiency in removing Total Nitrogen. Exploratory analysis of data for the two years studied show dendograms characterized by formation of groups have different type and characteristic result of the effluent generated during the production process in particular. The average efficiency station for removal of solids, COD, BOD, color, and phosphorus was 91%, 94%, 88%, 98% and 99% in 2009 and 95%, 95%, 95%, 99% and 98% in 2010, respectively, even with parameters ranging entry in the system was able to reduce them to values that met the legal requirements of CONAMA Resolution 357/2005.
Keywords: Tratamento de efluentes; Eficiência da estação; Demanda bioquímica de oxigênio; Microorganismos; Wastewater treatment; Efficiency of the station; Biochemical oxygen demand; Microorganisms; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA